Building and begging in Tbilisi. Contradictions in a Developing City - Roberta Pandolfino (Humanities)
This article aims to explore the relationship between apparent and real social development through the observation of vulnerable population segments. It argues that the landscape represents only a mystification of the true lifestyle in big cities. It examines Southern Caucasia, which has been home to conflictual scenarios and constant political, economic and social changes. Here post-Soviet urban loci present themselves as developing hubs. However, they house many beggars roaming their streets. This is a dichotomous, double reality that is magnified by magnificent new buildings and the exponential growth of urban centers. This reality is further exacerbated by an increasingly hungry population that is incapable (or incapacitated) of being part of the new socio-economic development project. Based on fieldwork, in-depth interviews and participant observation carried out in the second half of 2021, this research will examine the contradictions of the growing Georgian capital Tbilisi. These contradictions relate to an economic and demographic increase that does not represent the real welfare of the population. In Tbilisi, NGO’s have recently made informal practices a main means to engage with local authorities to attempt to provide missing services, and support the weakest, left behind population. The main purpose concerns the offer of a cultural and educational proposal that is opposed to street life. Here we explore several informal and undeclared economic and social practices: activities carried out by people who help other people informally and using public spaces as private in everyday life. All these practices become fundamental in an economy that wants to grow more and more focusing on the strongest but forgetting who lives on the margins. Here, informality becomes an indispensable tool for survival and growth.